Physico-Chemical, Viability Evaluations and Efficacy Assessment of Bacillus subtilis Against Soft Rot Disease in Phalaenopsis - Wakiah Nuryani; Hanudin Hanudin; Evi Silvia Yusuf; Kurniawan Budiarto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
The study of biological agents in controlling plant disease has discovered many potential microbes with various mode of actions. In the end, these potential microorganism should qualifiedly fulfill several requirements before they are formally stated for commercialization and wider implementation. Evaluations on their physico-chemical characteristics and viabililty after certain storage period were needed to ensure the effectiveness of the product during transportation and commercialization process. The research was aimed to evaluate B. subtilis strains B7 and B30 for their physio-chemical characteristic and viability after six months storage and investigate the efficacy of the strains against soft root disease of Phalaenopsis. The results showed that both antagonists had stable perfomances in physico-chemical, viability and efficacy evaluations after six months storage. The existence of active bacteria was demonstrated from the decrease in pH, murky suspensions and foul smelling as indications of fermentative reactions under optimal and minimal nutrients. Both antagonists showed stable viability after storage and effectively inhibited soft rot disease when applied on the infected plants with slightly lesser supression from streptomycin sulphate.